Kontribusi Locus of Control, Lingkungan Kerja Non-Fisik, dan Kedisiplinan terhadap Kepuasan Kerja pada Pegawai Pemerintah dengan Perjanjian Kerja (P3K) - Cahyadi, Irwan; Marlina, Febria Nurmelia; Anggriani, Rini (Distribusi - Journal of Management and Business, 2025)
Government Employees with Work Agreements (P3K) are employees with non-permanent status where the work period of the P3K depends on the contract given by the government. In addition, the P3K position is also limited to functional positions only, and does not receive old-age benefits (pension). This study aims to see the contribution of the variables of locus of control, non-physical work environment, and discipline to the job satisfaction of Government Employees with Work Agreements (P3K) who work at the Institute of Domestic Government (IPDN) West Nusa Tenggara Campus. This study is a quantitative study with an explanatory approach using 113 employees as respondents through the distribution of questionnaires. Furthermore, the data were analyzed using multiple linear regression analysis. The results of the study concluded that locus of control does not have a significant influence on employee job satisfaction, the non-physical work environment has a positive and significant influence on employee job satisfaction, and discipline has a positive and significant influence on employee job satisfaction. Based on the results of this study, institutions are expected to provide more appreciation and flexibility for the competencies possessed by employees so that it will increase employee self-confidence which will ultimately increase employee job satisfaction at the Institute of Domestic Government (IPDN) West Nusa Tenggara Campus.